SYNTHESIS AND CHARACTERIZATION OF POLYIMIDE-ZEOLITE MIXED MATRIX MEMBRANE - Tutuk Djoko Kusworo; Ahmad Fauzi Ismail; I Nyoman Widiasa; Seno Johari; Sunarso Sunarso; Budiyono Budiyono (Reaktor, 2009)
Biogas has become an attractive alternative energy source due to the limitation of energy from fossil. In this study, a new type of mixed matrix membrane (MMM) consisting of polyimide-zeolite was synthesized and characterized for biogas purification. The MMM consists of medium concentration of polymer (20% wt polyimide), 80% N-Methyl-2-pyrrolidone (NMP) and 25% zeolite 4A in total solid were prepared by a dry/wet phase inversion technique.  The fabricated MMM was characterized using SEM, DSC, TGA and gas permeation. Post treatment coating procedure was also conducted. The research showed that surface coating by 3% silicone rubber toward MMM PI 20% gave the significant effect to improve membrane selectivity. The ideal selectivity for CO2/CH4 separation increased from 0.99 for before coating to 7.9 after coating for PI-Zeolite MMM, respectively. The results suggest that PI-Zeolite MMM with good post treatment procedure will increase the membrane selectivity and permeability with more saver polymer requirement as well as energy saving due to low energy for mixing.